Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Synthesis and characterization of D-2PA-Pd(II)@SBA-15 catalyst via ``click chemistry'': highly active catalyst for Suzuki coupling reactions - Pathak, Aruna; Singh, A. P. (Journal of Porous Materials, 2017)
Copper catalysed cycloaddition reaction between azide and terminal alkyne, called as ``click reaction'', was found to be modular approach for the synthesis of facile, highly efficient and recoverable D-2PA-Pd(II)@SBA-15 catalyst. In efforts to synthesize the catalyst, the cycloaddition reaction between azido-functionalized mesoporous SBA-15 and N,N-dimethyl-2-propynylamine (D-2PA) has been carried out, followed by the complexation with PdCl2. To analyze physiochemical properties of synthesized materials, various characterization techniques such as CHN elemental analysis, X-ray diffraction, solid state C-13 and Si-29 NMR spectra, FT-IR, XPS, SEM, TEM and N-2 sorption analysis, TGA and DTA, UV-Vis spectroscopy have been carried out. The synthesized catalyst, D-2PA-Pd(II)@SBA-15, exhibited excellent catalytic activities with good product yield and high TON towards Suzuki coupling reaction of various aryl halides with phenylboronic acid. The effect of solvent, base and temperature on coupling reactions has also been described. The developed protocol offers recyclability of catalyst for multiple (four) times without any appreciable loss in stability and catalytic reactivity.
Keywords: Click reaction; Cycloaddition; mesoporous materials; SBA-15; Suzuki coupling

Crystal-to-crystal synthesis of helically ordered polymers of trehalose by topochemical polymerization - Hema, Kuntrapakam; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2020)
The synthesis of crystalline helical polymers of trehalose via topochemical azide-alkyne cycloaddition (TAAC) of a trehalose-based monomer is presented. An unsymmetrical trehalose derivative having azide and alkyne crystallizes in two different forms having almost similar packing. Upon heating, both the crystals undergo TAAC reaction to form crystalline polymers. Powder X-ray diffraction (PXRD) studies revealed that the monomers in both the crystals polymerize in a crystal-to-crystal fashion; circular dichroism (CD) studies of the product crystals revealed that the formed polymer is helically ordered. This solvent-free, catalyst-free polymerization method that eliminates the tedious purification of the polymeric product exemplifies the advantage of topochemical polymerization reaction over traditional solution-phase polymerization.
Keywords: Click reaction; helical polymers; polysaccharide; topochemical reactions; trehalose

Design and synthesis of C-α-D-mannopyranoside linked mesoporous silica nanoparticles - Nechooli, Hemanth K.; Ramtenki, Vilas; Kumar, Chepuri V. Suneel; Prasad, V. B. L.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2025)
Mannose functionalized mesoporous silica nanoparticles (MSNs) offer a promising approach for developing more targeted, effective, and safer cancer therapies. For many of the applications, immobilization of carbohydrates like mannose onto MSNs is a crucial aspect, and in most cases, mannose moieties are connected through O-glycosidic linkages that are susceptible to acidic/enzymatic hydrolysis. To generate a stable mannose-functionalized MSN, we designed a novel C(14)-alpha-mannosylated tetradeca-1-yne. The key steps involved in the synthesis of C-mannosylated alkyne are C1-alkynylation of tri-O-acetyl-D-glucal with 1-trimethylsilyl-tetradec-1-yne, followed by stereoselective dihydroxylation and the isomerization of the internal triple bond to a terminal position. This mannose ligand was then immobilized onto azidopropyl-functionalized SBA-15 through the Cu(I)-catalyzed azide-alkyne click (CuAAC) reaction. Various physical techniques such as low-angle powder XRD, N-2 adsorption isotherms (BET), Fourier transform infrared (FTIR), high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FE-SEM), and thermogravimetric analysis (TGA) have been employed to characterize this C-mannosyl SBA-15 silica matrix. We evaluated the binding ability of C-mannosyl SBA-15 nanoparticles by using fluorescein-labelled Con-A as a target protein.
Keywords: C-mannoside; Click reaction; mannose specific proteins; Mesoporous silica nanoparticles; Zipper reaction